GROWTH AND YIELD OF RUBBER TREE (Hevea brasiliensis) CLON PB260 FROM DIFFERENT OF WEED ECOSYSTEM - Habibulloh; M. Umar Harun; Firdaus Sulaiman (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2023)
Community rubber tree plantations in Indonesia are the main source of national natural rubber production and a source of income for farmers. Low rubber price has limit farmers' ability to control weeds using herbicides and mechanically. This situation causes the formation of three ecosystem conditions based on the level of weed growth, namely well-maintained plantations, shrubs on rubber plantations, and forests on rubber plantations. Therefore, this research studied and compared tree growth and rubber yields from three of weed ecosystems. Field research was designed using a Randomized Block Design (RBD) with three ecosystems as treatments and three replications. Three plots of size (10 m x 10 m) were made for each weed ecosystem in the rubber plantation, and three sam-pling rubber trees were selected so that the number of rubber trees observed was 9 trees for each ecosystem. Based on ANOVA, it showed that the weed ecosystem had a significant effect on the yield of rubber trees. Trees maintained well had the highest lumps (537 kg/6monts/ha), not significantly different from forested rubber trees (478 kg/6monts/ha. The dominant weeds in each ecosystem were Hevea brasiliensis and Acacia auriculiformis. Forested plantations had higher yields relatively more stable, producing lumps per week of 107.55 g/tree to 188.15 g/tree.